Evaluation of anti-inflammatory properties on the surface of dental implants depending on the type of processing (Part 1) - S. D. Varzhapetian; M. A. Shyshkin; T. V. Strogonova (Zaporozhye State Medical University, 2024)
The aim. To study of the anti-inflammatory properties of the surface of commercial dental implants with different processing methods using the example of the course of the first stage of implantation. Materials and methods. Dental implants made of titanium with 3D Active and Xpeed surface treatment were used. The surface microstructure and biocompatibility of the samples, surface corrosion, elemental analysis of the surface was studied. The assessment of the severity of peri-implantitis and mucositis based on the depth of the peri-implant pocket and bleeding during probing, determination of the coefficient of stability of implants (KSI) is given. Median test (χ2), Kruskel-Wallis test (H), univariate variance analysis (F) were used for multiple comparison of samples. The difference in parameters was considered statistically significant at the p ≤ 0.05 level. Results. The surfaces of 3D Active implants are monolithic with rounded pores in the form of wells of different diameters and depths; the upper layer of the Xpeed sample consists of closely adjacent to each other fragments of a rectangular or polygonal shape, in the form of tiles, leaving rectangular faces on the outside. On the surface of the 3D Active samples, in addition to oxygen and carbon, there was phosphorus - 5.04 wt%, as well as S, Ca, Na, Zr, Zn which weight percentage did not exceed 1 wt%. A significant difference in the elemental composition of Xpeed implants was the presence of chlorine 0.07 wt% and 0.93 wt%, silicon - 0.10 wt% and 0.14 wt%, aluminum 0.06 wt% and 0.23 wt%, respectively, with the latter has a significant advantage in these elements. Xpeed had an insignificant weight percentage of iron in its composition - 0.12 wt%. The assessment of cell adhesion to the surface of the samples on the first day of incubation demonstrated that the samples with the Xpeed and 3D Active surfaces did not have a statistically significant difference between them. Also, on the 7th day of incubation, the level of reduction of resazurin in Xpeed was lower, no significant difference was observed (p > 0.05). The clinical signs of bone tissue resorption were identified in 36.4 % of 3D Active implants and 60.0 % of Xpeed implants (p = 0.3); inflammation of the mucous membrane - in the areas of installation of 54.5 % of 3D Active implants. No signs of mucositis were detected around the Xpeed implants (p = 0.23). 9.1 % of 3D Active implants were "lost"; no cases of loss of Xpeed implants have been identified. The KSI of 3D Active - 64.0 ± 5.9 units, Xpeed - 65.1 ± 3.7 units. Conclusions. According to KSI indicators, titanium implants with Xpeed coating (65.1 ± 3.7 units) and 3D Active (64.0 ± 5.9 units) showed the same capabilities. Bone tissue resorption without signs of inflammation is more common around Xpeed-coated implants than 3D Active-coated implants. Clinical signs of inflammation are more frequent and more severe around implants with a 3D Active coating, which affected both the severity of the course of the first stage of implantation and its results. Xpeed-coated implants are more reliable than 3D Active: loss among 3D Active implants was 9.1 %, Xpeed - 0.0 %.